Coverage impacts biomass composition, conversion to ethanol yields and microbial communities during storage - Rigdon, Anne R. (Kansas State University, 2013)
Increased mandates for the production of transportation fuels from renewable resources have thrust the conversion of lignocellulosic biomass, e.g., energy crops and agricultural residues, to ethanol into commercial production. The conversion of biomass to ethanol has been implemented; transportation and storage logistics are still obstacles to overcome by industry. Limited harvest windows throughout the year necessitate extended periods of biomass storage to maintain a consistent, year-round supply to the biorefinery. Sorghum biomass stored with no coverage (NN), covered with tarp (NT), wrapped in plastic (PN) and covered with a tarp and wrapped in plastic (PT) for six months was analyzed for changes in biomass components—cellulose, hemicellulose and lignin, cellulose and hemicellulose degrading enzymes, and conversion to ethanol yields. Treatment NN had increased enzyme activity, and reduced cellulose content and ethanol yields; while biomass covered maintained enzyme activity, cellulose content and ethanol yields. Sequencing of the Large SubUnit (LSU) region and the internal transcribed spacer (ITS) regions of ribosomal RNA gene gave consistent results of fungal community dynamics in biomass stored as previously described. Fungal community richness and diversity increased, while evenness decreased in uncovered biomass during storage. Covered and uncovered storage treatments and over time were found to exhibit distinctly different fungal communities. In contrast, bacterial communities were found to be unresponsive to storage treatments and durations. Cladosporium, Alternaria and Cryptococcus were found to be the most abundant in the stored biomass. Covering of biomass strongly limits the arrival and establishment of new fungal propagules in stored biomass, reducing biomass degradation by these often pathogenic, saprobic or endophytic communities. Overall, covering of biomass during storage is essential for optimal substrate retention for downstream processing into ethanol. In addition, storage and transportation logistics of three real-world scenarios were evaluated for the conversion of wheat straw, corn stover and sorghum stalks residues to ethanol at a biorefinery located in Southwest Kansas. Economic evaluation revealed that transport and storage of residues at satellite storage facilities was most economical for farmers and would create opportunity for the operation of profitable facilities that would supply the local biorefinery on demand throughout the year.
Keywords: Lignocellulosic; Biomass; Ethanol; Storage; Fungi; Pyrosequencing; Agronomy (0285); Microbiology (0410)